2009
DOI: 10.21273/hortsci.19.4.813
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Horticulture Biology and Environmental Coastal Issues into the Middle School Science Curriculum

Abstract: Encouraging students to become better stewards of the environment and to be more educated in science content knowledge is an important goal of today's educational leaders. Eight lessons were created to aid an established stewardship program (Coastal Roots) in introducing hands-on activities to middle school children in southern Louisiana. Students were tested on science content in the lessons using a pre-test, eight multiple choice quizzes (each focusing on a particular lesson), and a post-test. The “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Skelly and Zajicek [16] also found time outdoors was a key predictor of pro-environmental attitudes in their evaluation of a gardening program. In Louisiana, horticulture teachers found that students participating in a program with an outdoor component were more aware of their role in the environment than students who did not participate in the program [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Skelly and Zajicek [16] also found time outdoors was a key predictor of pro-environmental attitudes in their evaluation of a gardening program. In Louisiana, horticulture teachers found that students participating in a program with an outdoor component were more aware of their role in the environment than students who did not participate in the program [17].…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the cause for limited evaluation, research addressing the drivers of EL is critical [22]. Although many studies examine factors contributing to at least one component of EL, [17], [23], [24], few if any address all four components or evaluate a broad suite of drivers. Efforts to standardize the way programs target and measure progress in all four elements include the National Environmental Literacy Assessment (NELA) project [7], [25] and the 2011 Framework for Environmental Literacy Assessment [6].…”
Section: Introductionmentioning
confidence: 99%
“…also found time outdoors was a key predictor of pro-environmental attitudes in their evaluation of a gardening program. In Louisiana, horticulture teachers found that students participating in a program with an outdoor component were more aware of their role in the environment than students who did not participate in the program (Karsh, Bush, Hinson, & Blanchard, 2009 (Palmer, 1998), and the Environmental Education Act of 1990 in the United States, which reestablished the Office of Environmental Education after its elimination in the 1980s (Palmer, 1998 Given the potential role of EL in addressing global environmental crises and the rapid expansion of EE around the world, there is surprisingly little empirical research addressing how EL is formed . Further, even less research utilizes beforeafter, treatment-control designs.…”
Section: Introductionmentioning
confidence: 99%
“…Whatever the cause for limited evaluation, research addressing the drivers of EL is critical (Palmer, 1999). Although many studies examine factors contributing to at least one component of EL, (Bradley, Waliczek, & Zajicek, 1999;Karsh et al, 2009;Lisowski & Disinger, 1991), few if any address all four components or evaluate a broad suite of drivers. Efforts to standardize the way programs target and measure progress in all four elements include the National Environmental Literacy Assessment (NELA) project McBeth et al, 2008) and the 2011…”
Section: Introductionmentioning
confidence: 99%
“…Many university-based horticulture departments explore the relationship between gardening programs and consumer knowledge and preferences. University-based programs in Louisiana and Texas (Karsh et al, 2009;Klemmer et al, 2005;Smith and Motsenbocker, 2005) studied student knowledge, environmental stewardship and confidence in science-based skills. These studies found positive correlations between garden participation and increased science scores and heightened environmental stewardship.…”
mentioning
confidence: 99%